High School Failure, a Systematic Review in the Social Sciences - Silvana Hernández-Ortiz (National Research Mordova State University, 2021)
Introduction. This study aims to examine the issue of high school failure in social sciences through a systematic review. It aims to provide a critical assessment of research on this subject. It seeks to question the very construct of high school failure, its premises, and the possible consequences from this perspective. Materials and Methods. The research published between 2010–2020, both in Spanish and English in the Scopus and Web of Science databases (Core collection), was considered. A total of 171 articles were identified. After initial screening, 37 papers were finally selected. Semantic maps were created with the Vosviewer. The literature was examined to determine where high school failure is being researched, what type of methodologies are most used and, finally, what impact the research has had on our understanding of this concept. Results. It was found that most of the research on the topic is done in the field of education, and that the methodology used is predominantly quantitative. The different definitions of high school failure tended to attribute its cause to one or more of four reasons: student failure, multicausal phenomena, social exclusion, and finally, disability in the education system. Discussion and Conclusion. It is possible to understand that high school failure is understood and defined as mostly involving studentsʼ responsibility for the academic outcome and achievement obtained. Although studies that cover such factors as a multicausal nature, social exclusion, and the education systemʼs difficulty can be found, the responsibility for failure tends to be attributed to the individual student.